2021
DOI: 10.5713/ab.21.0010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding intestinal health in nursery pigs and the relevant nutritional strategies

Abstract: In the modern pig production, pigs are weaned at early age with immature intestine. Dietary and environmental factors challenge the intestine, specifically the jejunum, causing inflammation and oxidative stress followed by destruction of epithelial barrier and villus structures in the jejunum. Crypt cell proliferation increases to repair damages in the jejunum. Challenges to maintain the intestinal health have been shown to be related to changes in the profile of mucosa-associated microbiota in the jejunum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 76 publications
(103 reference statements)
1
48
0
Order By: Relevance
“…The AID of DM and GE was negatively correlated with M. sualvi . The bacteria correlated with growth performance, intestinal health, and digestibility related in this study were previously reported by Duarte and Kim (2021) as key microbiota. Considering that growth performance is a multifactorial variable, it can be suggested that the shift of the microbiota should affect other parameters first and then affect growth performance indirectly.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The AID of DM and GE was negatively correlated with M. sualvi . The bacteria correlated with growth performance, intestinal health, and digestibility related in this study were previously reported by Duarte and Kim (2021) as key microbiota. Considering that growth performance is a multifactorial variable, it can be suggested that the shift of the microbiota should affect other parameters first and then affect growth performance indirectly.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the mucosa-associated microbiota is greatly susceptible to dietary influence in the small intestine of pigs ( Levesque et al, 2012 , 2014 ). Therefore, considering the digestive functions and the physicochemical properties in the small intestine, Duarte and Kim (2021) have showed that the mucosa of the jejunum could be considered a key site to evaluate the diet, intestinal microbiota, and intestinal health interaction. In this study, increasing levels of β-glucanase within diets containing xylanase reduced the abundance of the proteolytic bacteria H. rappini and increased the abundance of the fiber-degrading families Prevotellaceae , Lachnospiraceae , and Ruminococcaceae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrates, including PGN and TA, in the cell wall of Gram-positive bacteria can be used as sources of energy by intestinal microbiota and affect the diversity of the gut microbiota in humans and pigs ( Kaoutari et al, 2013 ; Kogut and Arsenault, 2016 ). High diversity is usually correlated with healthy status ( Bhandari et al, 2008 ; Fouhse et al, 2016 ; Kim and Duarte, 2021 ). However, in this study, the highest diversity was associated with the highest abundance of potential harmful bacteria and highest immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The second article, entitled 'Understanding intestinal health in nursery pigs and the relevant nutritional strategies' , by Kim and Duarte [2] discussed how piglets weaned at an early age with immature intestine (jejunum in particular) respond to dramatic changes in dietary and environmental factors. The study explained the challenges of maintaining a healthy status and growth potential of nursery piglets and defining biomarkers.…”
mentioning
confidence: 99%